EDUKASI PENGELOLAAN SAMPAH ORGANIK DENGAN PENDEKATAN EKO-ENZIM - Wijaya, Meiliyana (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Efforts to manage appropriate waste need to be followed up by the community to overcome the increasingly worrying effects of waste. There are many ways to manage waste, but downstream community awareness to take concrete action still needs to be improved. One way to manage waste is to make eco-enzymes. Eco-enzyme is a fermentation process using organic household waste, such as leftover vegetables and fruit which is then mixed with water and sugar to produce a mixture that resembles compost. Education about these eco-enzymes is essential so that the general public can practice this activity in the hope that the problems arising from waste will decrease. Even so, the public still does not know about eco-enzymes despite their enormous benefits. One educational method that is quite effective for introducing eco-enzymes during a pandemic is by holding online seminars. In addition, the video challenge method via Instagram regarding waste management is also a way to increase public awareness more interestingly and can be shared with online media audiences.